Long-term development and prediction of climate extremity and heat waves occurrence: Case study for agricultural land - VANÍČKOVÁ, Marta; STEHNOVÁ, Eva; STŘEDOVÁ, Hana (Contributions to Geophysics and Geodesy, 2017)
According to the IPCC it is possible to predict larger weather extremity associated with more frequent occurrence of heat waves. These waves have an impact not only on the health status of the population, on economic, social and environmental spheres, but also on agricultural landscape and production. The paper deals with the issue of climate extremity and addresses mainly the occurrence of characteristic days (tropical, summer, freezing, ice and arctic) and heat waves. The south-eastern Moravia belongs to the warmest regions of the Czech Republic. Since the area is not urban, it is not affected by urban heat islands. Thus, it can be used as a representative area of climate change in terms of weather extremes. Heat wave occurrence and length analysis was performed for the period of 1931–1960 and 1961–2013. In addition, a prospective analysis was carried out for the period of 2021–2100 where the scenario data of the Czech Hydrometeorological Institute were used. Between 1961 and 1990, heat waves appeared from June to September. The prediction for the next two decades shows that heat waves may appear as early as May. Furthermore, the average count of days in heat waves increased from 6.13 days (1961–1990) to 36 days (2071–2100). A statistically significant increase in the annual number of tropical days (from 9 to 20 days) was found in the assessment of characteristic days for the period 1961–2013. A highly conspicuous trend was found in July and a prominent trend was identified in May. A statistically highly significant trend was also observed in the annual number of summer days.